Soybean Seed Yield Productivity and Biological Nitrogen Fixation in Kansas - L. F. A. Almeida; A. A. Correndo; E. Adee; S. Dooley; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2022)
Soybean [Glycine max(L.) Merr.] productivity (seed yield) and biological nitrogen fixation (BNF) were evaluated in response to different fertilization strategies. The study comprised four different locations in Kansas during the 2021 growing season, two irrigated (Topeka and Scandia) and two dryland (Kiro and Ashland Bottoms) sites. Greater seed yields were recorded in Topeka and Kiro (80 bu/a) relative to Scandia (55 bu/a) and Ashland Bottoms (51 bu/a), without observing fertilizer effects on yields. Overall, the relative abundance of ureides (% RAU), an indicator of the level of BNF, increased as the crop matured and showed a negative association with the soil N level. The main objective of this study was to identify how different levels of nitrogen (N) and sulfur (S) fertilization affect the seed yield and the biological nitrogen fixation (BNF) in soybean.
Keywords: soybeans; biological nitrogen fixation; soil; weather; relative abundance of ureides